Hebella Allman 1888 - Schejter, L.; Genzano, G.; Pérez, C. D.; Acuña, F.; Cordeiro, R. T. S.; Silva, R. A.; Garese, A.; Bremec, C. S. (Zenodo, 2020)
Hebella sp. Material examined: BBB 2016: St. 5; St. 27; St. 32; St. 38; St. 39. Remarks: Scarce colonies attached on other hydroids ( Abietinella operculata and S. subdichotomus ) and on tubes of the polychaetes Chaetopterus antarcticus were found. Alike the genus Filellum , identification of Hebella to specific level is not possible when the material lacks reproductive structures. However the nominal species Hebella striata Allman, 1888 was widely reported in Argentinean continental shelf. : Published as part of Schejter, L., Genzano, G., Pérez, C. D., Acuña, F., Cordeiro, R. T. S., Silva, R. A., Garese, A. & Bremec, C. S., 2020, Checklist of Benthic Cnidaria in the SW Atlantic Ocean (54 ºS- 56 ºS), pp. 201-239 in Zootaxa 4878 (2) on page 210, DOI: 10.11646/zootaxa.4878.2.1, http://zenodo.org/record/4424884